Автоматические средства обнаружения и тушения пожаров - Герловин Ю. Н. Юрий Нисонович; Иванов Е. Н. Евгений Николаевич; Климов Г. В. Георгий Владимирович; Макаров В. М. Виктор Матвеевич (Москва, Стройиздат, 1974)
Исключено из фонда НТБ ТПУ